(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The study discusses the professional development of the individual, which is a multi-faceted process. The relevance of this work is defined by development trends that radically change the essence of professions on the labour market and require an understanding of the role of career guidance and professional self-determination as a single process throughout the entire working life of an individual. The study aims to investigate professional consciousness as a subjective component of professionalism and consider the algorithm for the development of professional self-consciousness in society. The study covers the main stages of professional development of the individual as a single process. The analysis of documents (monographs, websites, statistics, academic papers, and textbooks) was the objective method for the study. The study researched and systematised the leading approaches to discovering personal potential based on the collected material and identified all types of professional competence using the analysis method. As a result, the definition of factors of professionalism creates mental models of professional activity and the professional self-consciousness of the individual. The practical value of the study discussed and analysed the stages of development and establishment of a professional individual is implementing the results in the educational process and using the provided recommendations for creating a personal programme for mastering the course on the psychology of personality and professional development.